Management of sickle cell disease patients presenting to the emergency department with vaso-occlusive crisis: a retrospective study - Al Hussaini, Zainab Abdullah; Al Kanhal, Raghad; Al Ebrahaimi, Futoon; Al Shalhoub, Mohammed; Al Asmari, Bader; Othman, Fatmah (International Journal of Research in Medical Sciences, 2023)
Background: Sickle cell anemia (SCA) is a hereditary disease of the hemoglobin, characterized by recurring vaso-occlusive crises (VOC) leading to severe pain. VOCs constitute the primary cause for emergency department (ED) visits among sicklers. Frequent VOC episodes are associated with greater mortality. This study aimed to evaluate pain treatment trends regarding admission, discharge, length of stay in the ED, and early ED revisits among SCA patients. Methods: A cross-sectional study was conducted from January 2020 to January 2023 at the ED of King Abdulaziz medical city in Riyadh. SCA patients who presented with VOC episodes were included in this study. Demographic and clinical data of each patient were retrieved from the electronic medical file. Results: Total of 144 patients were included in the analysis. Out of the total population, 34% were admitted to hospital. Compared to those patients who were not admitted, the number of VOC was more among patients who had been admitted. Around 34% had ED revisit within 30 days and those patients had higher frequency of VOC attacks compared to those who did not revisit the ED. Only 45% of the population received appropriate dosing, 30% received an insufficient dose, and 25% received over the appropriate dose. Receiving the correct dose of morphine reduced the likelihood of ED revisits within 30 days. Conclusions: This study explores trends in VOC among sticklers, highlighting that adequate analgesia is associated with better outcomes. Addressing these variables may lead to improved care and better outcomes for SCA patients.